Does mobile phone use of women during pregnancy cause hearing problems in infants? Preliminary observation - Bektaş, Hava; Daşdağ, Süleyman; Bektaş, Mehmet Selçuk (Perinatal Medicine Foundation, 2020)
Objective Some studies have claimed that long-term conversation with mobile phones can cause hearing loss. However, it has not been investigated whether exposure to mobile phones during pregnancy affects the hearing of babies in the womb. Therefore, the aim of this human study was to investigate the effects of intrauterine radiofrequency radiation (RFR) exposure emitted from mobile phones on the hearing of newborns. Methods The study population comprised 149 newborns. Pregnant women in this study were divided into 4 groups according to RFR exposure duration, such as non-exposure to RFR, exposure to RFR for 2-15 min/day, exposure to RFR for 15-60 min/day, and exposure to RFR for more than 60 min/day. The results of the hearing screening analyses of the newborns, which were performed using transiently evoked otoacoustic emission and auto auditory brainstem response, were investigated retrospectively. Results The results of this study indicated that 900 and 1800 MHz RFR exposure during pregnancy did not cause hearing loss in newborns. Conclusion In conclusion, we observed that the hearing sensitivity and peripheral sound perception of newborns were not affected by RFR exposure emitted from mobile phones during the intrauterine period. Further studies should be performed to illuminate the subject.